CONTENT ANALYSIS OF THE CHEMISTRY BOOK FOR THE SECOND INTERMEDIATE GRADE IN IRAQ IN LIGHT OF SCIENTIFIC DEVELOPMENTS - Al-Bayati, Kareem Ahmed Mohammed (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to analyze the content of the second-grade chemistry curriculum in Iraq in light of recent scientific developments. Method: The researcher employed a descriptive-analytical approach. The researcher prepared a list of scientific innovations to be used as a curriculum analysis tool, aiming to determine the extent to which the curriculum incorporates these innovations. Results: The statistical results supported the hypothesis, showing that the chapters of the second intermediate grade chemistry textbook differ in their treatment of scientific innovations. In some chapters of the book, the coverage of scientific innovations reaches up to approximately 30%, indicating a higher concentration of these innovations in specific chapters compared to others. Novelty: The study identifies the varying extent to which scientific innovations are incorporated across different chapters of the second-grade chemistry curriculum, highlighting a concentration of innovations in certain chapters up to approximately 30%.